1982
DOI: 10.1145/1006258.1006286
|View full text |Cite
|
Sign up to set email alerts
|

Initial thoughts on rapid prototyping techniques

Abstract: This paper sets some context, raises issues, and provides our initial thinking on the characteristics of effective rapid prototyping techniques. After discussing the role rapid prototyping techniques can play in the software lifecycle, the paper looks at possible technical approaches including: heavily parameterized models, reusable software, rapid prototyping languages, prefabrication techniques for system generation, and reconfigurable test harnesses. The paper concludes that a multi-faceted approach to rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Prototyping as a technique is usually seen as a supplement to conventional application systems development methodologies (Taylor and Standish 1982 ;Vonk 1990 ) . It emphasises on high user participation and tangible representations of selected user requirements at an early stage.…”
Section: Prototypingmentioning
confidence: 99%
“…Prototyping as a technique is usually seen as a supplement to conventional application systems development methodologies (Taylor and Standish 1982 ;Vonk 1990 ) . It emphasises on high user participation and tangible representations of selected user requirements at an early stage.…”
Section: Prototypingmentioning
confidence: 99%
“…Over the years, several studies have confirmed these tripartite aspects of the software crisis. For example, in relation to development time-scales: Flaatten et al (1989) estimated development time for the average project to be about 18 months -a conservative figure perhaps given that other estimates put the figure at about three years (Business week 1988) or even up to five years (Taylor and Standish 1982). Also, an IBM study estimated that 68 per cent of projects overran schedules (Bowen 1994).…”
Section: Software Crisis 10mentioning
confidence: 99%
“…Summarizing very briefly, the principal weakness of the SDLC is that later phases depend on the successful completion of earlier phases, which requires 'perfect foresight' (Henson & Hughes, 1991). However, later phases are much more likely to take place in the context of 'imperfect predecessors' (Taylor & Standish, 1982). Researchers have noted that systems developrn&t in practice is not an orderly systematic phased process (Wastell & Newman, 1993) but tends to happen all at once (De Grace & Stahl, 1993).…”
Section: Inadequacies Of the Rational Scientific Paradigmmentioning
confidence: 99%
“…The conceptualization of development as following a linear sequence of phases is implicit in the systems development life-cycle (SDLC). However, the SDLC approach has come in for considerable criticism (McCracken & Jackson, 1981;Taylor & Standish, 1982;Glass, 1991;Henson & Hughes, 1991). Summarizing very briefly, the principal weakness of the SDLC is that later phases depend on the successful completion of earlier phases, which requires`perfect foresight' (Henson & Hughes, 1991).…”
Section: Inadequacies Of the Rational Scientific Paradigmmentioning
confidence: 99%